Perencanaan Daya Tampung Bendungan Budong - Budong Kabupaten Mamuju Tengah - Mohammad Noer Akbar Sabri; Burhanuddin Badrun; Andi Rumpang Yusuf (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Dam construction is very necessary for irrigation, raw water supply and flood control, the main requirement for its construction is its stability. If stability is not met, it will trigger dam safety problems such as leaks, seepage, landslides, erosion and cracks. So, it is necessary to plan capacity by measuring the elevation, area and volume of several layers by involving literature studies, determining data requirements, providing administrative requirements, data collection from related agencies, and site surveys as an illustration of field conditions. The data is processed to obtain cumulative volume and presented in a table. Analysis of the water capacity of the Budong- budong dam in Central Mamuju Regency, West Sulawesi Province, is important in planning and managing water resources. The results of this research indicate that the Budong - Budong dam was built with a storage capacity of 57,284,568 m3 at an elevation of 70+. The dam was built using a type of rock fill dam with a clay core, due to the availability of sufficient rock material around the dam location.